Boron-doped MnTe semiconductor-sensitized ZnO solar cells - Tubtimtae,A. (Indian Academy of Sciences, 2015)
© Indian Academy of Sciences. We studied the photovoltaic performance of boron-doped MnTe semiconductor-sensitized solar cells (B-doped MnTe SSCs). The B-doped MnTe semiconductor was grown on ZnO using two stages of the successive ionic layer adsorption and reaction (SILAR) technique. The two phases of B-doped semiconductor nanoparticles (NPs), i.e. MnTe and MnTe2 were observed with a diameter range of approximately 15-30 nm. The result of the energy conversion efficiency of the sample with boron doping was superior compared to that of an undoped sample, due to the substantial change in the short-circuit current density and the open-circuit voltage. In addition, plots of (αhν)2 vs hν with band gaps of 1·30 and 1·27 eV were determined for the undoped and B-doped MnTe NPs, respectively. It can be noted that the boron doping effects with the change in the band gap and lead to an improvement in the crystalline quality and also intimate contact between the larger sizes of MnTe NPs. Hence, a noticeably improved photovoltaic performance resulted. However, this kind of semiconductor sensitizer can be further extended by experiments on yielding a higher power conversion efficiency and greater stability of the device.